Chronic citalopram effects on the brain neurochemical profile and perfusion in a rat model of depression detected by the NMR techniques - spectroscopy and perfusion - Harastova-Pavlova, Iveta; Drazanova, Eva; Kratka, Lucie; Amchova, Petra; Hrickova, Maria; Macicek, Ondrej; Vitous, Jiri; Jirik, Radovan; Ruda-Kucerova, Jana (Biomedicine & pharmacotherapy, 2024)
BACKGROUND: Major depressive disorder (MDD) is a mental illness with a high worldwide prevalence and suboptimal pharmacological treatment, which necessitates the development of novel, more efficacious MDD medication. Nuclear magnetic resonance (NMR) can non-invasively provide insight into the neurochemical state of the brain using proton magnetic resonance spectroscopy (1H MRS), and an assessment of regional cerebral blood flow (rCBF) by perfusion imaging. These methods may provide valuable in vivo markers of the pathological processes underlying MDD. METHODS: This study examined the effects of the chronic antidepressant medication, citalopram, in a well-validated MDD model induced by bilateral olfactory bulbectomy (OB) in rats. 1H MRS was utilized to assess key metabolite ratios in the dorsal hippocampus and sensorimotor cortex bilaterally, and arterial spin labelling was employed to estimate rCBF in several additional brain regions. RESULTS: The 1H MRS data results suggest lower hippocampal Cho/tCr and lower cortical NAA/tCr levels as a characteristic of the OB phenotype. Spectroscopy revealed lower hippocampal Tau/tCr in citalopram-treated rats, indicating a potentially deleterious effect of the drug. However, the significant OB model-citalopram treatment interaction was observed using 1H MRS in hippocampal mI/tCr, Glx/tCr and Gln/tCr, indicating differential treatment effects in the OB and control groups. The perfusion data revealed higher rCBF in the whole brain, hippocampus and thalamus in the OB rats, while citalopram appeared to normalise it without affecting the control group. CONCLUSION: Collectively, 1H MRS and rCBF approaches demonstrated their capacity to capture an OB-induced phenotype and chronic antidepressant treatment effect in multiple brain regions.
Keywords: Depressive Disorder, Major; deprese; Brain metabolites; Depression; mozek; Rats; Cerebral perfusion; zvířata; Animals; Olfactory bulbectomy; bulbus olfactorius; citalopram; Male; protonová magnetická rezonanční spektroskopie; magnetická rezonanční spektroskopie; mužské pohlaví; depresivní porucha unipolární; potkani Sprague-Dawley; Olfactory Bulb; Disease Models, Animal; Magnetic Resonance Spectroscopy; modely nemocí na zvířatech; Rats, Sprague-Dawley; Brain; Cerebrovascular Circulation; hipokampus; Hippocampus; krysa rodu Rattus; Citalopram; mozkový krevní oběh; Proton Magnetic Resonance Spectroscopy